2012
DOI: 10.1021/bi3001616
|View full text |Cite
|
Sign up to set email alerts
|

Helix-Dipole Effects in Peptide Self-Assembly to Amyloid

Abstract: The formation of amyloid fibrils is associated with incurable diseases including Alzheimer's, Parkinson's, and type 2 diabetes. Important mechanistic details of the self-assembly are unknown partly because of the absence of a clear structural characterization of intermediates. There is experimental evidence, however, for α-helical intermediates that has come primarily from circular dichroism spectroscopy. Here, we strengthen the evidence for helical intermediates by demonstrating helix-dipole effects in the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Finally, deamidation at positions 31 and 35 did not affect the time necessary to reach the high-energy nucleus, the rate of amyloid growth, or the morphology of the assemblies. These data reinforce the concept that the 11–25 segment mediates the initial intermolecular interactions leading to amyloid assembly. , …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Finally, deamidation at positions 31 and 35 did not affect the time necessary to reach the high-energy nucleus, the rate of amyloid growth, or the morphology of the assemblies. These data reinforce the concept that the 11–25 segment mediates the initial intermolecular interactions leading to amyloid assembly. , …”
Section: Discussionsupporting
confidence: 85%
“…These data reinforce the concept that the 11−25 segment mediates the initial intermolecular interactions leading to amyloid assembly. 45,46 It was previously reported that nontargeted and spontaneous (aging) Asn deamidation accelerates IAPP self-assembly and alters fibrils structure. 18 However, the Asn residues subjected to deamidation were not identified.…”
Section: ■ Discussionmentioning
confidence: 99%
“…34 Their further experimental studies strengthened the existence of α -helical intermediates in amyloid formation of hIAPP(11–25) and full-length hIAPP peptides. 35,36…”
Section: Introductionmentioning
confidence: 99%
“…The success of deconvolution, however, depends primarily on the availability of reference databases that include CD spectra of proteins of known structure . Because current databases do not include CD spectra of peptide or protein assemblies, deconvolution may not be applicable to the analysis of CD spectra of amyloidogenic peptides and proteins. ,, Nonetheless, if the protein assembly of interest is predominantly α-helical, a suitable alternative to deconvolution is to use eq , which has been successfully applied to determine the helix content of α-helical assemblies: where [θ] 222nm is the mean-residue ellipticity of the peptide at 222 nm and [θ] 222nm,100%helix is the calculated mean-residue ellipticity at 222 nm of a peptide with a helix content of 100%. To calculate the latter, we used the following equation derived by Chen et al: where [θ] 222nm,infinite helix is the mean-residue ellipticity at 222 nm for an infinite helix determined by Chen et al to be equal to −37 400 deg cm 2 dmol –1 , k is a wavelength-dependent factor that is equal to 2.5 at 222 nm, and n helix is the number of residues in the helix.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we investigated a fragment of IAPP that forms an α-helix in order to explore the role of the helix dipole in the self-assembly of amyloidogenic peptides in the presence of membranes. IAPP is a 37-residue polypeptide (Figure ) that is cosecreted with insulin from pancreatic β-cells.…”
Section: Introductionmentioning
confidence: 99%